Making Science Public as a route to better evidence - Pearce, Warren; Raman, Sujatha (LSE, 2013)
It is widely accepted that scientific evidence should play a role in policy decisions, yet the form that this should or could take remains subject to intense debate. Warren Pearce and Sujatha Raman discuss how the Making Science Public project attempts to address these questions.